Ethical issues relating the the banking of umbilical cord blood in Mexico - Valdez-Martinez Edith; Novello-Garza Barbara; Serrano-Delgado V Moises (BMC Medical Ethics, 2009)
Abstract Background Umbilical cord banks are a central component, as umbilical cord tissue providers, in both medical treatment and scientific research with stem cells. But, whereas the creation of umbilical cord banks is seen as successful practice, it is perceived as a risky style of play by others. This article examines and discusses the ethical, medical and legal considerations that arise from the operation of umbilical cord banks in Mexico. Discussion A number of experts have stated that the use of umbilical cord goes beyond the mere utilization of human tissues for the purpose of treatment. This tissue is also used in research studies: genetic studies, studies to evaluate the effectiveness of new antibiotics, studies to identify new proteins, etc. Meanwhile, others claim that the law and other norms for the functioning of cord banks are not consistent and are poorly defined. Some of these critics point out that the confidentiality of donor information is handled differently in different places. The fact that private cord banks offer their services as "biological insurance" in order to obtain informed consent by promising the parents that the tissue that will be stored insures the health of their child in the future raises the issue of whether the consent is freely given or given under coercion. Another consideration that must be made in relation to privately owned cord banks has to do with the ownership of the stored umbilical cord. Summary Conflicts between moral principles and economic interests (non-moral principles) cause dilemmas in the clinical practice of umbilical cord blood storage and use especially in privately owned banks. This article presents a reflection and some of the guidelines that must be followed by umbilical cord banks in order to deal with these conflicts. This reflection is based on the fundamental notions of ethics and public health and seeks to be a contribution towards the improvement of umbilical cord banks' performance.